Insights into computational analysis of HIV-1 reverse transcriptase resistance to non-nucleoside Inhibitors: Efavirenz, Etravirine, Nevirapine and Rilpivine - AMEERUDDIN NUSRATH UNISSA,; LUKE ELIZABETH HANNA, (International Journal of Pharma and Bio Sciences, 2017)
Reverse transcriptase (RT) is a crucial enzyme for the process of transcription in type-1 human immunodeficiency virus (HIV-1). Inhibitors of RT enzyme can be divided into two distinct classes: nucleoside analogue RT inhibitors (NRTIs) and non-nucleoside RT inhibitors (NNRTIs). The drugs that belong to NNRTI bind to a hydrophobic pocket close to the active site of RT, which causes allosteric inhibition of the reverse transcription process. Resistance to NNRTIs such as efavirenz (EFV), etravirine (ETV) nevirapine (NVP), and rilpivine (RPV) is a frequent event. The most common mutations associated with all NNRTIs resistance is G190A. It is of interest to know the basis of RT resistance caused by this mutation (G190A). In this study, the mutant (MT) G190A of RT was modeled and docked with NNRTIs such as EFV, ETV, NVP, and RPV in comparison to the wild-type (WT). The MT model was built using the template 3MEC of HIV-1 RT. The results of docking indicate that the WT showed high score with all inhibitors compared to the MT-G190A. On the basis of the results it can be suggested that the high affinity in WT could be attributed to the favorable interactions with all inhibitors that lacks in MT- G190A. In other words, due to amino acid substitution from Gly in WT to Ala in MT containing an extra methyl group that lead to structural changes which alters the interaction network in the MT protein in comparison to WT, so as to impart resistance against all inhibitors.